Conceptually integrating a multi-product strategy for the valorization of kitchen waste towards a more sustainable management. (15th July 2021) - Wu, Mengke; Hu, Jinguang; Shen, Fei; Huang, Mei; Zhao, Li; Tian, Dong; Zhang, Yanzong; Liu, Yan; Zeng, Yongmei; Deng, Shihuai
Abstract: Disposal of kitchen wastes (KW) by anaerobic digestion (AD) is popular for many currently running projects, but the discharged residual solid fraction from three-phase separation is challenging the AD process in the real world. To cope with the challenge, a multi-product strategy, including bacterial cellulose (BC) production and vermicomposting, was integrated into the currently running AD process to be a new process; the as-prepared biochar from vermicompost was attempted in AD to promote the digestion performances. Experiential investigations on the multi-product strategy, LCA (life cycle assessment) and economic assessment on the integrated process were performed to clarify the technical compatibility, environmental sustainability, and economic profitability. Results showed that 1.0 t kW (wet basis) yielded 4.5 kg earthworm biomass, 20.0 kg vermicompost, and 0.8 kg BC (dry basis), suggesting the multi-product strategy was compatible to the valorization of residual solid fraction. Cumulative CH4 was promoted by 31.0% via adding as-prepared biochar in AD of liquid fraction from separation and effluent from BC fermentation, indicating the technical compatibility of the techniques of BC production, vermicomposting and AD. LCA demonstrated the newly integrated process reduced the GWP (Global Warming Potential) and AP (Acidification Potential) emission by 40.9% and 130.0%; net output of PED (Primary Energy Demand) increased by 32.8%, suggesting its environmental sustainability was promoted comparing to the currently running process. Besides, 3.0% promotion on the net revenue of the newly integrated process implied the increased profitability. As a result, the newly integrated process will be a step forward towards a more sustainable management on KW. Graphical abstract: Image 1 Highlights: Kitchen waste (KW) is valorized for vermicomposting & bacterial cellulose (BC). 1.0 t kW yields 0.8 kg BC, 4.5 kg earthworm biomass and 20.0 kg vermicompost (VC). 31% CH4 yield is promoted by adding biochar prepared from VC in anaerobic digestion. Integrating vermicomposting, BC, biochar with anaerobic digestion for KW disposal. The newly integrated process is more sustainable and profitable for managing KW.